The feasibility of through-the-cycle ratings - Karlo Kauko (Bank of Finland, 2010)
It has been proposed that the potential procyclicality of Basel II could be alleviated by using through-the-cycle (TTC) ratings in IRBA models. A TTC rating would be based on the structural component of the debtor s credit risk ignoring cyclical fluctuations. This paper tests for the existence of such fluctuations in corporate sector credit risk and finds vietually no evidence for their existence at the company level. It is not possible to assign satisfactory TTC ratings to debtors if there are no cyclical variations to be filtered out.
URN:NBN:fi:bof-20140807295
Keywords: G21; G33; L16; 330; through-the-cycle rating; credit risk; procyclicality